Comparison Of The Effectiveness Of Moringa Leaf Tea And Rosella Flower Tea On Reducing Blood Pressure In Mild Hypertension Patients : Case Study - Wahyuni, Tri (CV. Literasi Publikasi Indonesia, 2024)
The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that every year 9.4 million people die from hypertension and its complications. This case study aims to compare the effectiveness of Moringa leaf tea and Rosella flower tea in reducing blood pressure in menopausal women who experience mild hypertension. The research respondents were 2 menopausal women who suffered from mild hypertension, one respondent was given intervention in the form of Moringa leaf tea while the other respondent was given intervention in the form of rosella flower tea. The intervention was provided for 14 days to see a comparison of the effectiveness of the two interventions provided. The reduction in blood pressure in respondents with the Moringa leaf tea intervention was 15/11 mmHg, while the reduction in blood pressure in respondents with the rosella flower tea intervention was 7/7 mmHg, there was a difference in blood pressure of 8/4 mmHg. Thus, it can be concluded that giving Moringa leaf tea is more effective in reducing blood pressure in menopausal women with mild hypertension compared to giving rosella flower tea. Moringa leaf tea can be developed as an alternative therapy to lower blood pressure in people with mild hypertension.